Comparison of the Physical Activity of 11–12 Year Old Pupils in Two Schools in Norway and Iceland, using Pedometer Registrations and Activity Diaries - Hallås, Bjørg Oddrun; Herfindal, Torunn; Wergedahl, Hege (2014)
Detailed knowledge about physical activity (PA) in both school and leisure time is of great importance in order to promote children’s health. This study investigated and compared the PA levels of sixth-grade pupils, 11–12 years of age, in two Nor-dic schools, during both school and leisure time by combining pedometer meas-ures with activity diary records. Pupils from Norway (n= 44) and Iceland (n=37) wore pedometers for seven consecutive days and kept an activity diary for the first two days. After pupils’ PA had been registered for one week using a pedometer, no significant differences in pedometer step counts were found. Nor were there signi-ficant differences in the pedometer step counts between weekdays and weekends. But when looking only at the group of pupils reporting to meet the standard of at least 60 minutes PA and 12,000 pedometer step counts per day for girls and 15,000 for boys, results revealed that there were a higher percentage of Norwegian pupils in this group. However, within this group the Icelandic pupils were active for a longer period and had higher pedometer step counts. The Norwegian pupils re-ported a significantly higher daily PA from walking or cycling to school than the Icelandic pupils. Among boys, there were no other significant differences. On the other hand, the Norwegian girls reported a significantly higher level of exercise in sports club and a significantly lower level of leisure time walks than the Icelandic girls. In conclusion, although the total amount of PA of Norwegian and Icelandic pupils was similar, a closer look at the various activities during school time and leisure time revealed significant differences between the case schools, including gender differences. Our study has contributed to the knowledge about PA among 11–12-year-old pupils in two Nordic countries. The results of our study have re-vealed a need for more research into different factors, in both school and leisure time that can contribute to increasing Nordic pupils PA levels. Nákvæm þekking á ...